A review of selected studies assessing nurses’ knowledge of pressure injury prevention - Bazaliński, Dariusz; Sałacińska, Izabela; Przybek-Mita, Joanna; Kawalec, Anna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2025)
The scope of nursing competencies in selecting methods and measures for the prevention and treatment of pressure injuries is extensive. To provide effective and safe care for patients with wounds, nursing staff should possess high qualifications and comprehensive knowledge. The objective of the article is to analyze the literature on pressure injury prevention among nurses. The collected material was categorized into the following themes: nurses’ knowledge and education in pressure injury prevention, evidence-based prevention strategies, and the role of the clinical leader in addressing pressure injury prevention. Most of the analyzed studies emphasize that the effectiveness of pressure injury prevention depends on nurses’ level of knowledge and their professional functioning. In conclusion, prevention, along with regular staff training, should be prioritized in the healthcare sector. Clinical decision-making should be based on current scientific evidence and present a range of options to facilitate collaboration between healthcare professionals, patients and the entire interdisciplinary team.